Asketiske rum i Koranen og tidlig islamisk Muhammadbiografi: Om et overset fænomen i askese-studier - Hoffmann, Thomas (Religionsvidenskabeligt Tidsskrift, 2016)
Focusing on the Qur’ān and the early biographical literature on Muhammad, I present the thesis that asceticism takes on a special spatial expression in Islam. This is expressed in three types of ’cramped’ and ‘fixated’ spatiality: 1) in concrete physical form, 2) in language and literature, and 3) in ritualized embodiment. This thesis I link theoretically to more recent research in spatiality, particularly Edward Soya’s conceptualization of First-, Second-, and Thirdspaces. Finally, I fit this in with the paradoxical and far-reaching argument that these cramped and fixed spatialities, which find expression in introvert and world-eschewing First- & Secondspaces, ultimately give rise to a Thirdspace with highly extrovert and revolutionary potentials. In addition, I introduce briefly to the concept of asceticism and its treatment (and lack thereof) within three subject areas, i.e., research in Late Antiquity, research in the so-called Axial Age, and Islamic/Qur’ānic studies.